Penerapan Akuntansi Manajemen Berbasis Aktivitas Pada Perusahaan Manufaktur di Kawasan GIIC - Ayu Nengsih; Purwanti (CV. ITTC INDONESIA, 2025)
This study was conducted with the aim of analyzing the application of Activity Based Management, namely to improve cost efficiency in manufacturing companies in the GIIC Area. The research method used is a qualitative method. Based on the analysis that has been used by implementing Actifity Based Management, it has a positive impact on the company in order to obtain the expected cost efficiency so that it can increase the profits generated by the company. And to achieve this goal, the company must carry out several stages, then in addition to that by implementing Actifity Based Management the company can save costs incurred by the company. Activity Based Management emphasizes activity management or activity analysis, in its application